2003
DOI: 10.1086/378932
|View full text |Cite
|
Sign up to set email alerts
|

RHESSI Observations of Particle Acceleration and Energy Release in an Intense Solar Gamma-Ray Line Flare

Abstract: We summarize Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI) hard X-ray (HXR) and gray imaging and spectroscopy observations of the intense (X4.8) g-ray line flare of 2002 July 23. In the initial rise, a new type of coronal HXR source dominates that has a steep double-power-law X-ray spectrum and no evidence of thermal emission above 10 keV, indicating substantial electron acceleration to tens of keV early in the flare. In the subsequent impulsive phase, three footpoint sources with much flatter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
193
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 449 publications
(208 citation statements)
references
References 38 publications
14
193
0
1
Order By: Relevance
“…For the purpose of comparison, we examined a quasi-steady reconnection event discovered in the solar wind 12 and found that the acceleration of electrons is absent (not shown). Our findings strongly suggest that the very strong acceleration observed during substorms 30 and impulsive solar flares 31 occurs during unsteady reconnection.…”
supporting
confidence: 65%
“…For the purpose of comparison, we examined a quasi-steady reconnection event discovered in the solar wind 12 and found that the acceleration of electrons is absent (not shown). Our findings strongly suggest that the very strong acceleration observed during substorms 30 and impulsive solar flares 31 occurs during unsteady reconnection.…”
supporting
confidence: 65%
“…Since 2002, the RHESSI mission (Ramaty and Mandzhavidze, 2000;Lin et al, 2003;Hurford et al, 2003), provides high-resolution imaging and spectroscopy from soft X-rays to Gamma-rays. New results are being published in a fast pace (see the ADS for authors like Lin, Krucker, Hudson, Hurford and others).…”
Section: Hard X-raysmentioning
confidence: 99%
“…• Solar flare observations allowed measurements of flare spectra and in particular excited-particle flow geometries [ 27,43,7].…”
Section: Resultsmentioning
confidence: 99%